Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am wondering two different forms of the second mean value theorem for integration. For the one in wikipedia, I also wonder where I can find a proof.

The form I read from another reference is that: $G:[a,b]\to \mathbb{R}$ is a monotonic function and $\phi : [a, b] \to \mathbb{R}$ is an integrable function, then there exists a number $x$ in $[a, b]$ such that

$$\int_a^b {G(t)\phi(t)}dt=G(a)\int_a^x{\phi(t)dt}+G(b)\int_x^b{\phi(t)dt}.$$

Note the difference in where $x$ lies and whether to use the one-side limit for $G(a)$ and $G(b)$. To me, I think whether $G$ is right continuous at $a$ or left continuous at $b$ should not matter the integral $$\int_a^b {G(t)\phi(t)}dt$$, but clearly $G(a)$ vs. $G(a+)$ can be quite different.

I am wondering if anyone can give me a proof that the two are equivalent. Thanks.

share|cite|improve this question
up vote 4 down vote accepted

Some notations. First, for every $x$ in $[a,b]$, let $F(x)=\displaystyle\int_a^x\phi(t)\mathrm{d}t$, hence $F$ is continuous and $F(a)=0$. Second, assume that $G$ is nondecreasing, the other case being similar. Thus there exists a nonnegative measure $\mu$ such that, for every $x$ in $[a,b]$, $G(x)=G(a)+\displaystyle\int_a^x\mathrm{d}\mu(t)$.

Now to the proof. Using an integration by parts, the integral $I$ of $G\phi$ over $[a,b]$ is $$ I=[F(t)G(t)]_a^b-\int_a^bF(t)\mathrm{d}\mu(t)=F(b)G(b)-\int_a^bF(t)\mathrm{d}\mu(t). $$ The hypothesis made on $G$ means that $\mu$ is a nonnegative measure hence the first mean value theorem for integration yields the existence of a point $x$ in $[a,b]$ such that $$ \int_a^bF(t)\mathrm{d}\mu(t)=F(x)\int_a^b\mathrm{d}\mu(t)=F(x)(G(b)-G(a)). $$ Coming back to $I$, one gets $$ I=F(b)G(b)-F(x)(G(b)-G(a))=G(a)F(x)+G(b)(F(b)-F(x)), $$ which, by definition of $F$, is the desired assertion.

(No continuity of $G$ is required.)

In case you are wondering, the first mean value theorem used above is not the usual one but it has the same proof than the usual one. Namely, $F$ being continuous on the compact set $[a,b]$ has a maximum $M$ and a minimum $m$ on $[a,b]$, thus $$ m\int_a^b\mathrm{d}\mu(t)\le\int_a^bF(t)\mathrm{d}\mu(t)\le M\int_a^b\mathrm{d}\mu(t). $$ (This step uses the hypothesis that $\mu$ has constant sign.) In other words, there exists $u$ in $[m,M]$ such that $$ \int_a^bF(t)\mathrm{d}\mu(t)=u\int_a^b\mathrm{d}\mu(t). $$ Now, the continuity of $F$ implies that there exists $x$ in $[a,b]$ such that $u=F(x)$ and you are done.

Previous version When $\phi$ has a constant sign, this is a consequence of the intermediate value theorem. (An earlier version of this post did not assume $\phi$ of constant sign, hence an argument was wrong. Thanks to the OP for having asked some explanations.)

Let $I$ denote the integral of $G\phi$ over $[a,b]$, $J$ the integral of $\phi$ over $[a,b]$, and $H(x)$ the RHS of the equality you want to prove. Assume that $\phi$ is nonnegative and $G$ is nondecreasing, the other cases being similar.

Since $G(a)\le G(t)\le G(b)$ and $\phi(t)\ge0$ for every $t$ in $[a,b]$, $G(a)\phi(t)\le G(t)\phi(t)\le G(b)\phi(t)$ for every $t$, hence $G(a)J\le I\le G(b)J$. The function $x\mapsto H(x)$ is continuous on the interval $[a,b]$, $H(a)=G(b)J\ge I$ and $H(b)=G(a)J\le I$, hence by the intermediate value theorem there exists $x$ in $[a,b]$ such that $H(x)=I$.

(No continuity of $G$ is required.)

share|cite|improve this answer
Good one. Come to think: why is the proof I studied was so long and tedious? I mean, it's just i.v.t... XD – Pacciu Mar 23 '11 at 18:25
I did not quite follow your proof. When you say "inequality", what did you mean? I read it as "equality". Also I did not follow why "Since $G(a)\le G(t)\le G(b)$ for every $t$ in $[a,b]$, $G(a)J\le I\le G(b)J$." Looks like you are using some other theorem/result? I also did not expect $J$ to be positive. – Qiang Li Mar 24 '11 at 2:56
Revised version. Below the line is a modification of the former proof, valid only for functions $\phi$ of constant sign. Above the line is a proof of the general case. The new ingredient is an integration by parts which transforms the monotonicity hypothesis on $G$ into a constant sign property. Thanks for the comment. – Did Mar 24 '11 at 7:52

The statement of the second m.v.t. I use to know concerns continuous functions, so its proof rely on the first m.v.t. for continuous functions. Hence I had to work out a new proof... And, quite surprisingly, it seems that both $G(a),G(b)$ and $G(a^+),G(b^-)$ work in the equality.

Therefore, maybe there is something wrong in my proof... You have to check carefully. ^^

Proof: Let $G,\phi:[a,b]\to \mathbb{R}$ be bounded and Riemann integrable over $[a,b]$ and $G(x)$ be decreasing. It is obvious that it suffices to prove that there exists $\xi ,\eta \in [a,b]$ s.t.:

$\int_a^b \phi G =G(a^+)\int_a^\xi \phi =G(a)\int_a^\eta \phi$

for nonnegative $G(x)$, because if $G(x)$ takes both positive and negative values, then $G(x)-G(b^-)$ and $G(x)-G(b)$ are nonnegative (the former is negative in only $b$, but a point is negligible w.r.t. integration).


$l_k:=\inf_{[x_k,x_{k+1}]} \phi,\ L_k :=\sup_{[x_k,x_{k+1}]} \phi$

$m_k:=\inf_{[x_k,x_{k+1}]} G,\ M_k :=\sup_{[x_k,x_{k+1}]} G$

and note that the range of $\phi(x) G(x)\Big|_{[x_k,x_{k+1}]}$ is $\subseteq [\min \{ l_k m_k,l_k M_k\}, \max \{ L_k m_k, L_k M_k\}]=:I_k$. Let $D=\{a=x_0<x_1<\ldots <x_n<x_{n+1}=b \}$ be a partition of $[a,b]$ and write the Riemann sum:

$\sigma_D (\lambda_0\mu_0,\ldots ,\lambda_n \mu_n) :=\sum_{k=0}^n \lambda_k \mu_k (x_{k+1}-x_k)$,

where $\lambda_k\in [l_k,L_k],\ \mu_k \in [m_k, M_k]$ (so that $\lambda_k\mu_k \in I_k$): it is well known that $\sigma_D(\lambda_k\mu_k) \to \int_a^b \phi G$ when the diameter of $D$ shrinks to $0$ independently on how we choose $\lambda_k, \mu_k$.

Now set $\Phi (x):=\int_a^x \phi$ and choose $\lambda_k$ s.t. $\lambda_k (x_{k+1}-x_k)=\int_{x_k}^{x_{k+1}}\phi =\Phi(x_{k+1}) -\Phi (x_k)$ (which is possible for the first m.v.t.): therefore the Riemann sum rewrites:

$\sigma_D(\lambda_k\mu_k)=\sum_{k=0}^n \mu_k [\Phi (x_{k+1})-\Phi (x_k)] = \sum_{k=0}^{n-1} (\mu_k -\mu_{k+1})\Phi (x_{k+1}) + \mu_{n} \Phi (x_{n+1})$.

$\Phi(x)$ is a bounded function in $[a,b]$ (for $\phi$ is), and the differences $\mu_-\mu_{k+1}$ are nonnegative (because $G(x)$ decreases one has $m_k\geq M_{k+1}$, and $\mu_k \in [m_k,M_k], \mu_{k+1}\in [m_{k+1},M_{k+1}]$), therefore:

(*) $p\mu_0 \leq \sigma_D(\lambda_k \mu_k)\leq P\mu_0$,

where $p:=\inf_{[a,b]} \Phi$ and $P:=\sup_{[a,b]} \Phi$.

Now it is clear that in (*) one can choose $\mu_0$ arbitrarily: in particular, one can choose $\mu_0=G(a^+)$ or $\mu_0=G(a)$, and in each case, one gets an uniform bound (w.r.t. $D$) for $\sigma_D(\lambda_k,\mu_k)$.

Finally, letting the diameter of $D$ tend to $0^+$, one has:

$p\mu_0\leq \int_a^b\phi G \leq P\mu_0$,

hence applying the first m.v.t. to the continuous function $\Phi(x)$ one has the claim, with two different point $\xi,\eta$ (in general) depending on the choice of $\mu_0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.